Hubungan Kepuasan Konsumen Terhadap Pelayanan Bengkel Motor di Desa Kasiyan - Wahid Aljauzi, M Nur Rafli; Iwan Musthofa Habibullah, Dovi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
The motorbike repair shop services in East Kasiyan village show differences in the level of customer satisfaction. People who depend on motorbike repair shops for motor vehicle maintenance and repair often judge the quality of the services provided based on several factors, such as technician skills, service times, and available facilities. This research aims to analyze the level of consumer satisfaction with motorbike repair services in East Kasiyan Village, as well as identifying the factors that influence this satisfaction. The research results show that the quality of technicians and service time are the main factors that influence the level of consumer satisfaction. Most customers are satisfied with the results of repairs, however there are several complaints regarding workshop facilities and service prices which are considered high. This research provides new findings regarding the importance of comfort and price aspects in determining consumer satisfaction in rural areas. The novelty of this research lies in an in-depth analysis of the factors that influence customer satisfaction in village motorbike repair shops which may not have been widely researched before.